Sleep Expression Category in Arabic: A Morphosemantic Approach - Alif Cahya Setiyadi; Anhar; Riza Nurlaila; Maram Traf (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
The Arabic language is renowned for its immense richness and depth. It is widely recognized as one of the world's most intricate and expressive languages. This richness stems from several factors, including its extensive vocabulary, complex grammar, and diverse linguistic features. Despite Arabic's reputation for linguistic depth, there is limited morphosemantic analysis focusing on the variety of Arabic nouns derived from verb-root patterns that express sleep. This study aims to investigate these sleep-related nouns to uncover the diverse roots, meanings, and classifications that demonstrate the richness of Arabic vocabulary in this semantic field. This article presents a morphosemantic investigation to determine the verb-root pattern of sleep nouns from which the noun construction originates. The study comprises three main stages. Firstly, each sleep expression is extracted by consulting an online and a classical Arabic dictionary to identify their basic root. Secondly, the meanings of all aforementioned sleep-noun expressions are determined based on the same dictionary. Lastly, the categorization of Arabic sleep nouns is established. This study's findings reveal at least twenty distinct basic roots that convey the concept of sleep in Arabic, each with its unique and distinguishable meaning. These expressions can then be classified into three categories: Durations, Stages, and Time.